A Comprehensive Review Of Disaster Mitigation And Geoeducation: Approaches And Future Researches - Prantoko, Edi; Muslim, Dicky; Yosep, Boy (UNIVERSITAS PAKUAN, 2019)
Geoeducation plays a critical role in promoting public understanding of geological processes, conservation, and disaster mitigation through education. This comprehensive review examines the trends and approaches used in geoheritage education, emphasizing its potential in disaster risk reduction. A bibliometric analysis of 192 documents from Scopus (2020–2024) is followed by an in-depth content analysis of selected studies. The findings highlight a variety of educational methods, including field-based learning, media-based platforms (such as documentaries and virtual reality), and museum-based education. While these approaches show promise, several gaps in the research are identified, such as the limited integration of advanced digital technologies, a lack of long-term impact studies, underutilization of geoheritage in formal education, and insufficient interdisciplinary perspectives, particularly in relation to disaster mitigation. The study emphasizes the need for future research to address these gaps and suggests that more comprehensive, interdisciplinary, and innovative approaches, including the integration of disaster risk reduction, can enhance the effectiveness of geoeducation in promoting conservation, mitigation, and societal engagement with geoheritage